Is Open Science a Developed Countries’ Phenomenon? A Case Study of Journals Registered in the DOAJ - Patra, Swapan Kumar; Roy, Udita (Journal of Data Science, Informetrics, and Citation Studies)
The open science movement is a significant development recently that promotes equality, accessibility, and transparency in research. The program aims to improve the quality and significance of research while increasing public access to science. The open science movement advocates for free and open science using various means. This novel idea gained focus since its conception during last few decades. Open access to scholarly content is a prerequisite to excel in research. Open access to research through scholarly journals is a subset of open science. This paper is an attempt to analyse journals listed on the Directory of Open Access (DOAJ) repository. The study observed that there is growth in open access journals globally. However, most of the journals are from the developed countries. This is because high-income nations with superior facilities and infrastructure benefited from a variety of incentives to publish in open access journals or various modes of open access. So, it can be argued that open science is a developed countries’ phenomenon. Middle and lower-middle groups of countries should encourage various forms of open science, including the open access of scholarly content through scholarly publications. Further insight into the scholarly publication patterns, including the subject coverage, citation analysis, and author-level collaboration analysis, will yield a better and holistic picture of the phenomenon.
Keywords: Open Science; Open Access; Directory of Open Access Journals; DOAJ; Creative Commons; CC Licences.